Translating Finnish Education to Indonesia: Barriers and Adaptation Strategies in High Schools - Ahmad Hadi Pranoto; Ikhrom Ikhrom; Raharjo Raharjo; Mahfud Junaedi; Faiz Abdul Majid Assharofi (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Finnish education model is widely recognized for its holistic, flexible, and student-centered approach. However, its implementation in other contexts, such as Indonesia, presents significant structural and cultural challenges. This study explores how secondary school teachers in Indonesia understand Finnish educational principles, the obstacles they face in adopting them, and the strategies they employ for contextual adaptation. A qualitative phenomenological design was used to capture teachers' lived experiences. Data were collected through in-depth interviews, classroom observations, and document analysis at three secondary schools in Central Java, representing diverse institutional and socio-cultural contexts. Thematic analysis was conducted through open coding, axial coding, and selective coding. The study identified three major barriers to adaptation: institutional rigidity, incompatibility with the prevailing learning culture, and limitations in educational infrastructure. Teachers demonstrated varying levels of understanding of Finnish principles, influenced by their training and school environment. Adaptation strategies included implementing interest-based projects, promoting flexible learning methods, and fostering more humanistic teacher–student relationships. The findings suggest that adapting Finnish educational values in Indonesia is not a matter of replication but requires contextual translation. Successful implementation depends on sustained teacher professional development, culturally responsive curriculum design, and policy support that enables flexibility while addressing local constraints. Finnish educational principles can inspire meaningful innovation in Indonesian schools when adapted thoughtfully. Building a supportive ecosystem through training, policy, and cultural sensitivity is key to bridging global models with local realities.